Stone diet and dietary change: understanding determinants for dietary change behaviour in patients following urinary stones - Muhamad, Suhana; Sowtali, Siti Noorkhairina; Mohd Arifin, Siti Roshaidai; Ab Rashid, Islah Munjih; Mohd Shukri, Nor Azwani (The British Dietetic Association Ltd, 2023)
Background: Dietary habit is one of the most important methods to prevent and treat urinary stones. However, only limited evidence of the experiences of dietary management among urinary stone patients in Malaysia is available. This study aimed to explore participants' current dietary practices after the diagnosis of urinary stones and to identify the factors that facilitate their dietary changes. Methods: A qualitative study with purposive sampling was conducted using face‐to‐face semistructured interviews. A total of 20 participants from a tertiary general hospital in Kuantan, Malaysia, were recruited in this study. Data were analysed using framework analysis. Results: Two themes emerged from the analysis. The first theme explained the changes in the dietary practice of the participants postdiagnosis. The second theme revealed that the participants' dietary changes were greatly influenced by personal factors and external support from professionals, family and peers. Conclusions: Urinary stone patients highlighted the fear of complications, self-determination and knowledge of nutrition as the main drivers of their dietary change postdiagnosis. Emphasising proper nutritional care by assessing and evaluating dietary self‐management among patients can facilitate effective selfcare in stone prevention management.